Manipulation of the energy metabolism of ruminants in the tropics: options for improving meat and milk production and quality - Ku Vera, J. C.; Brice?o, E. G.; Ruiz, A.; Mayo, R.; Ayala, A. J.; Aguilar, C. F.; Solorio, F. J.; Ram?rez, L. (Cuban Journal of Agricultural Science, 2014)
Ruminant feeding in tropical regions is characterized by grass grazing. Throughout the year, grasses show variations in their availability and quality. Therefore, modern feeding systems must consider the energy requirements of the animal and the degree in which a feed or a combination of several of them could cover the nutritional requirements of the different species and physiological conditions. The central reaction for obtaining energy is carry out in the rumen in the anaerobic fermentation of the carbohydrates present in the feed. Thisprocess is developed by the ruminal microorganisms, with the purpose of generating energy for the microbial growth and the concomitant production of volatile fatty acids, methane, carbon dioxide and fermentation heat. For improving meat and milk production and quality in tropical regions, different options have been created for manipulating the energy metabolism of ruminants. Silvopastoral systems, based on Leucaena leucocephala and Panicum maximum association, allow attaining live weight gains of 770 g/d in growing cattle. It is essential the identification of Bos indicus cattle breeds or crosses with lower requirements of metabolizable energy (ME) for maintenance, so as the energy efficiency of meat production could be increased. For milk, it is possible to increase the concentration of unsaturated fatty acids (CLA?s) by the tannin presence in the foliages that due to its beneficial effect on human health, could supply aggregate value to the cow?s milk. Feeding practices are necessary for reducing the caloric increase of the feeding and that decrease methane emissions from the rumen through the effect of some foliages and fruits that possess secondary metabolites capable of affecting ruminal fermentation. Key words: energy metabolism, tropical feeds, ruminants